Architecture and mathematics in ancient Egypt - Rossi, Corinna (Cambridge University Press, 2004)
In this fascinating study, architect and Egyptologist Corinna Rossi analyses the relationship between mathematics and architecture in ancient Egypt by exploring the use of numbers and geometrical figures in ancient architectural projects and buildings. While previous architectural studies have searched for abstract 'universal rules' to explain the history of Egyptian architecture, Rossi attempts to reconcile the different approaches of archaeologists, architects and historians of mathematics into a single coherent picture. Using a study of a specific group of monuments, the pyramids, and placing them in the context of their cultural and historical background, Rossi argues that theory and practice of construction must be considered as a continuum, not as two separated fields, in order to allow the original planning process of a building to re-emerge. Highly illustrated with plans, diagrams and figures, this book is essential reading for all scholars of Ancient Egypt and the architecture of ancient cultures
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte Antike; Architektur; Mathematik; Architecture, Ancient / Egypt; Architecture / Egypt / Mathematics; Pyramids / Egypt; Kunst; Ägypten; Ägypten -- Altertum